HUBUNGAN ANTARA USIA DAN PARITAS DENGAN KEJADIAN CA SERVIKS DI RSUD JAILOLO - Mansur, Juharti; Retnaningsih, Reny; Alim, Zainal (NHM PRESS, 2024)
Cervical cancer is one of the most common cancers suffered by women throughout the world, including Indonesia. This disease is caused by human papillomavirus (HPV) infection and attacks cervical tissue. Even though HPV vaccination and screening programs are available, cervical cancer is still a major health problem in many countries, including Indonesia. This article provides an overview of cervical cancer, including risk factors, symptoms, diagnostic methods, and prevention strategies that can be used to reduce the burden of this disease. According to the World Health Organization (WHO), cervical cancer is the main cause of cancer deaths among women in developing countries (WHO, 2020). However, cervical cancer can mostly be prevented with HPV vaccination and regular check-ups with pap smears and HPV tests. Routine screening is an effective way to detect precancerous changes in the cervix, allowing for early treatment before cancer develops (American Cancer Society, 2021). This research has a sample of 16 people using a quasi-experimental research type with a posttest only control group design. Based on the results of statistical data analysis using the Spearman's test with SPSS, the result was a value (asymptotic Sig 2-sided) p-value = <0.006. It can be concluded that H0 is rejected and Ha is accepted, which means there is a Relationship Between Age And Parity And The Incident Of Cervical Ca At Jailolo Hospital